Early recognition of the APECED rash can accelerate the diagnosis of APECED - Elise M.N. Ferré; Chyi-Chia R. Lee; Michail S. Lionakis (Clinical Immunology Communications, 2024)
Autoimmune-Polyendocrinopathy-Candidiasis-Ectodermal Dystrophy (APECED) is a monogenic autoimmune disease most often resulting from biallelic loss-of-function variants in the autoimmune regulator (AIRE) gene. Although typically characterized by the classic triad of chronic mucocutaneous candidiasis, hypoparathyroidism, and adrenal insufficiency, we have recently reported that the clinical spectrum of the syndrome is far broader that previously described and that incorporation of an adjunct triad of APECED rash, autoimmune enteritis-associated intestinal dysfunction, and enamel hypoplasia in the classic triad manifestations could lead to earlier diagnosis. Among the adjunct triad manifestations, APECED rash occurs in 66 % of American APECED patients by age 3, most often developing in the first year of life. Here, we describe the clinical and histological features of protracted APECED rash manifesting together with recurrent mucocutaneous candidiasis as the first two disease components of APECED in a 10-month-old girl.